TINGKAT KENYAMANAN PADA BEBERAPA TAMAN KOTA DI KOTA MATARAM: The Comfort Level at Various Park in Mataram City - Diah Permata Sari; Kornelia Webliana B.; Maiser Syaputra (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Mataram city on Lombok Island as a local and foreign tourist destination has several cityparks as part of a green open space in urban areas that serves to support the comfort oftourism in the Mataram city. Analysis of the level of comfort in several city parks withthe function of tourism and sports in the Mataram city is important. The data taken inthis study consisted of primary data in the form of temperature and humidity data.Temperature and humidity measurements at each city park are measured using athermometer and hygrometer. Based on the Temperature Humidity Index (THI) value orthe Comfort Index value, Udayana Park, Selagalas Park and Sangkareang Park areincluded in the medium comfort category with THI values less than 27, while TamanMayura is included in the uncomfortable category with THI values more than 27.Keywords: Comfort levels, city parks, temperature and humidity